Skyline queries over incomplete multidimensional database - Alwan, Ali Amer; Ibrahim, Hamidah; Udzir, Nur Izura; Sidi, Fatimah (Universiti Utara Malaysia Press, 2011)
In recent years, there has been much focus on skyline queries that incorporate and provide more flexible query operators that return data items which are dominating other data items in all attributes (dimensions). Several techniques for skyline have been proposed in the literature. Most of the existing skyline techniques aimed to find the skyline query results by supposing that the values of dimensions are always present for every data item. In this paper we aim to evaluate the skyline preference queries in which some dimension values are missing. We proposed an approach for answering preference queries in a database by utilizing the concept of skyline technique. The skyline set selected for a given query operation is then optimized so that the missing values are replaced with some approximate values that provide a skyline answer with complete data. This will significantly reduce the number of comparisons between data items. Beside that, the number of retrieved skyline data items is reduced and this guides the users to select the most appropriate data items from the several alternative complete skyline data items.